ETHICS OF THE STATE CIVIL APPARATUS IN PROVIDING PUBLIC SERVICES IN AN EFFORT TO REALIZE GOOD GOVERNANCE - Herijanto Bekti (SEAN Institute, 2021)
Ethical behavior and effective leadership go hand in hand. In order to achieve good governance, it is necessary to have ethical values that serve as guidelines and must be followed by the public and public administrators. One of the problems that arises in the provision of public services is that there are still deviations by the State Civil Apparatus, hereinafter referred to as ASN in public services. To better understand how public administration ethics can be applied to the delivery of public services and ultimately promote good governance, this research is focusing on the state's civil apparatus. This research is a qualitative study using a descriptive approach to analyze and clarify phenomena in the field. According to the study's findings, in order to meet the needs of the community in a variety of service capacities, the apparatus as a public administrator has a duty to ensure that citizens have access to high-quality public services. Problems with management in the public sector abound. No one ever tells customers how much a service will cost or how long it will take. This happens because citizens' rights as service recipients and service providers' responsibilities are never codified in the procedures by which these interactions take place. Establishing public service standards is a workable solution. Developing a Complaint Management System, Customer Satisfaction Survey, and Standard Operating Procedures..